The Mini-TRH Test - Spoov, Johan (Pharmacopsychiatry, 2022)
Thyrotropin-releasing hormone (TRH), at doses lower than those needed to stimulate prolactin secretion directly, can almost completely antagonize dopamine inhibition of prolactin release. In normal men, prolactin increases 15 min following an i. v. bolus of 12.5 µg TRH (the mini-TRH test), but not the maximal prolactin response to TRH or basal prolactin, positively correlated with prolactin response to haloperidol and negatively with 24-h urinary excretion of homovanillic acid (HVA). These results suggest that the mini-TRH test is a better estimate of dopamine inhibition of prolactin release than the maximal prolactin response or basal prolactin level. A recent neuroimaging study suggested that in schizophrenia, there is a widely distributed defect in extrastriatal dopamine release, but the patients were not in the most acute phase of psychosis. The evidence is reviewed that this defect extends to tuberoinfundibular dopamine (TIDA) and which symptoms are associated with the test. In patients with acute nonaffective psychosis, the mini-TRH test positively correlated with nonparanoid delusions and memory dysfunction, indicating decreased dopamine transmission in association with these symptoms. In patients with acute drug-naïve first-episode schizophrenia, the mini-TRH test negatively correlated with negative disorganization symptoms and with basal prolactin. The latter correlation suggests the contribution of factors related to maximal prolactin stimulation by TRH; therefore, an alternative dose of 6.25 μg TRH could be used for the mini-TRH test in first-episode patients, allowed by increased sensitivity of the present prolactin tests. Future studies are needed to investigate whether the mini-TRH test could help in finding the optimal antipsychotic medication.
Keywords: mini-TRH test; dopamine; prolactin; schizophrenia; extrastriatal